2021
DOI: 10.1039/d1ra01904j
|View full text |Cite
|
Sign up to set email alerts
|

Directional mass transfer of azo molecular glass microsphere induced by polarized light in aqueous immersion media

Abstract: Directional mass transfer of azo molecular glass microspheres is comprehensively investigated upon polarized light irradiation in various aqueous immersion media, and the key factors to influence mass transfer and shape deformation are elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…[59,60] Microstructured azobenzene materials, such as microparticles and pillars, are able to deform in response to polarized light, elongating in the polarization direction. [61,62] Therefore, we hypothesized that the blister formation could also be photo-controlled.…”
Section: Photo-control Over Blister Shape and Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…[59,60] Microstructured azobenzene materials, such as microparticles and pillars, are able to deform in response to polarized light, elongating in the polarization direction. [61,62] Therefore, we hypothesized that the blister formation could also be photo-controlled.…”
Section: Photo-control Over Blister Shape and Formationmentioning
confidence: 99%
“…The deformation of bulk microspheres, for instance, has been studied both in air and water, and differences in the deformation were observed. [61,88] In particular, the higher the refractive index of the immersion medium, the more prominent the mass transport parallel to the substrate. Furthermore, in bulk microspheres and pillars the deformation took place only at the top surface due to the high absorbance of the material and the consequent rapid light attenuation inside the particle, leading to mushroom-shaped structures.…”
Section: Photo-controlled Blister Shape and Formationmentioning
confidence: 99%
“…Depending on irradiation duration and the concentration of the AZOPD fraction, the relative stretching quantity ranges between 10–70%, which is comparable with results from literature. Comparable experiments show relative stretching ranges between 30–140% [ 38 , 39 , 48 , 49 , 50 ]. However, a small degree of degradation was obtained after the second reversion, which is observable in a decrease in the -ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The major research on directional stretching of micro- and nanostructures containing azo materials has been done with azo polymers because of their diverse properties ranging from amorphous to liquid crystalline features [ 15 , 18 , 28 , 32 , 33 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. However, it was shown that low molecular azo glasses are good candidates for directional photo-induced deformation, too [ 37 , 47 , 48 , 49 , 50 , 51 ]. In comparison to polymers, the synthesis of azo glasses allows an advantageous control for uniform molecular weight.…”
Section: Introductionmentioning
confidence: 99%